Cryopreserved human umbilical cord patch for in‐utero spina bifida repair. (2nd February 2016) - Papanna, R.; Moise, K. J.; Mann, L. K.; Fletcher, S.; Schniederjan, R.; Bhattacharjee, M. B.; Stewart, R. J.; Kaur, S.; Prabhu, S. P.; Tseng, S. C. G.
ABSTRACT: Objective: To identify a patch system to repair surgically created spina bifida in a sheep model for its efficacy in healing the skin defect, protecting the underlying spinal cord and reducing the Chiari II malformation. Methods: Spina bifida was created surgically in 16 fetuses from eight timed‐pregnant sheep at gestational age of 75 days. Two fetuses did not survive the procedure. Repeat hysterotomy was performed at 95 days' gestation to cover the defect with either biocellulose film with underwater adhesive (BCF‐adhesive) ( n = 7) or human umbilical cord with suture (HUC‐suture) ( n = 7). Three fetuses without formation of the defect served as reference controls. The skin healing was examined by direct visualization after a planned Cesarean section at term, followed by histological analysis using hematoxylin and eosin and Masson's trichrome stains. Mid‐sagittal sections of the fetal cranium and upper cervical spine were analyzed by a pediatric neuroradiologist who was blinded to the type of patch received. Results: Three fetuses that received the BCF‐adhesive and six fetuses that received the HUC‐suture survived to term for final analysis. As a result of dislodgment of the BCF‐adhesive, all spina bifida defects repaired using BCF‐adhesive were not healed and showed exposed spinal cord with leakage of cerebrospinal fluid. In contrast, all spinal defects repaired by HUC‐suture were healed with complete regrowth of epidermal, dermal and subdermal tissue components, with no exposed spinal cord. The maximal skin wound width was 21 ± 3.6 mm in the BCF‐adhesive group but 3 ± 0.8 mm in the HUC‐suture group ( P < 0.001). The spinal cord area ( P = 0.001) and the number of anterior horn cells ( P = 0.03) was preserved to a greater degree in the HUC‐suture group than in the BCF‐adhesive group, whilst psammoma bodies, signifying neuronal degeneration, were only observed in the BCF‐adhesive group. Anatomic changes, indicative of Chiari II malformation, were seen in all three fetuses of the BCF‐adhesive group but in none of the HUC‐suture group ( P < 0.01). Conclusion: Cryopreserved umbilical cord graft is a promising regenerative patch for intrauterine repair of spina bifida. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.